A Retrospective Analysis of the House Prices Macro-Relationship in the United States - Ahamada, Ibrahim; Diaz Sanchez, Jose Luis (World Bank, Washington, DC, 2013)
This study provides empirical evidence on the strengthening of the impact of house prices on the US macroeconomy. The stability of the house prices macro-link is tested in a small-dimensional vector autoregressive model over the last fifty years. The estimated break-points are used to split the sample into different segments and a multivariate time series analysis is performed within subsamples. The paper finds a robust structural break in the mid-1980s. In addition, time series analysis across segments provides evidence that the effect of house prices, not only on private consumption, but also on economic activity, has intensified since the mid-1980s.